1996
DOI: 10.1099/0022-1317-77-2-369
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of human T cell lymphotropic virus type I to human term trophoblast cells in vitro

Abstract: We studied the susceptibility of term placental trophoblast cells to in vitro infection with human T cell leukaemia/lymphotropic virus type I in order to provide further insight into the role of syncytiotrophoblast in transplacental passage of the virus. Pure villous trophoblast cultures were exposed to cell-free virus and the extent of infection was analysed by semiquantitative PCR assay to detect integrated proviral DNA. Four different primer pairs targeting the gag, pol, env and pX regions invariably reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…However, we found that HTLV-1 provirus was detected in the cord blood and placental villous tissues. We also tested sensitivity to HTLV-1 in the cells of the blood-placental barrier and found increased susceptibility to HTLV-1 infection in the VTs in accordance with previous reports (55)(56)(57). In addition, our study showed that HTLV-1 directly infected VTs in pregnant carriers and that HTLV-1 RNA was expressed at a high level in some of these infected cells.…”
Section: Discussionsupporting
confidence: 90%
“…However, we found that HTLV-1 provirus was detected in the cord blood and placental villous tissues. We also tested sensitivity to HTLV-1 in the cells of the blood-placental barrier and found increased susceptibility to HTLV-1 infection in the VTs in accordance with previous reports (55)(56)(57). In addition, our study showed that HTLV-1 directly infected VTs in pregnant carriers and that HTLV-1 RNA was expressed at a high level in some of these infected cells.…”
Section: Discussionsupporting
confidence: 90%
“…Maternal blood immunoglobulins G (IgGs) are carried across the placenta by receptor-mediated transcytosis into fetal blood (24,36). Trophoblastic cells also form the first efficient barrier to protect the fetus from maternal infection, but its efficiency depends on the pathogen (28,38,55,56). Data concerning the permissivity of purified primary trophoblasts or trophoblastic cell lines to cellfree HIV infection remain controversial (18,32,43,47,62,63).…”
mentioning
confidence: 99%
“…In in vitro experiments, exposure of the cell-free HTLV-1 virus to trophoblasts did not result in infection [71]. Recently, Tezuka et al demonstrated that during pregnancy of HTLV-1 carriers, HTLV-1 was highly expressed in placental villous tissues, and villous trophoblasts showed high HTLV-1 sensitivity compared to that in other component cells (mesenchymal fibroblasts and placental vascular endothelial cells) of the blood-placental barrier.…”
Section: Transplacental Htlv-1 Transmissionmentioning
confidence: 99%